2015
DOI: 10.1007/s12194-015-0318-1
|View full text |Cite
|
Sign up to set email alerts
|

Practical calibration curve of small-type optically stimulated luminescence (OSL) dosimeter for evaluation of entrance skin dose in the diagnostic X-ray region

Abstract: For X-ray diagnosis, the proper management of the entrance skin dose (ESD) is important. Recently, a small-type optically stimulated luminescence dosimeter (nanoDot OSL dosimeter) was made commercially available by Landauer, and it is hoped that it will be used for ESD measurements in clinical settings. Our objectives in the present study were to propose a method for calibrating the ESD measured with the nanoDot OSL dosimeter and to evaluate its accuracy. The reference ESD is assumed to be based on an air kerm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…We used optically stimulated luminescence (OSL) dosimeters (NanoDot, Landauer, Inc., Glenwood, IL) [19][20][21] (Fig. 1).…”
Section: Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…We used optically stimulated luminescence (OSL) dosimeters (NanoDot, Landauer, Inc., Glenwood, IL) [19][20][21] (Fig. 1).…”
Section: Dosimetrymentioning
confidence: 99%
“…However, because the mixing ratio of direct and scattered X-rays differs depending on the organ placement under the usage conditions in this study, it is difficult to determine the effective energy of the X-ray field inside the human body exactly. According to the previous research 19 , it has shown that the uncertainty is at most 15% when the manufacturer-determined calibration factor is used to analyze doses using X-rays at other tube voltages. Furthermore, a study has been reported in which the dose determined by the OSL dosimeter using this method shows the correct entrance surface dose during CT examination within the margin of error 20 .…”
Section: Dosimetrymentioning
confidence: 99%
“…Reports concerning thermo‐luminescent dosimeters, 26 alanine/electron spin resonance (ESR) dosimeters, 27 and optically stimulated luminescence (OSL) dosimeters 25,28–35 have been published. In this study, we focused our attention on the OSL dosimeter, which is composed of Al 2 O 3 :C, because this dosimeter has good characteristics for dosimetry in the medical field 31,36,37 . Currently, a commercial OSL dosimeter, named nanoDot TM OSL dosimeter, is being used for medical applications 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The nanoDot OSL dosimeters are widely used for patient dose measurement in the medical field, and many papers on the basic characteristics of nanoDot OSL dosimeter exposed to less than 10 Gy have been reported [4][5][6]. There are also some literatures concerning the patient dose evaluation during radiation diagnosis [7][8][9]. On the other hand, there are a few papers to study the dose response characteristics of OSL dosimeters exposed to more than 10 Gy [10][11][12].…”
Section: Introductionmentioning
confidence: 99%